Zinc lysine and selenium yeast can effectively improve the reproductive performance of Northeast white geese - Jingchun Li; Heze Feng; Yulun Song; Hechuan Wang; Yingying Dong; Han Li; Qing Guo; Shengjun Liu; Yanbing Li (Poultry Science)
The aim of this study was to investigate the effects of dietary supplementation with selenium yeast (YS) and zinc lysine (ZL) on goose semen quality, testicular tissue structure, reproductive hormone levels, antioxidant capacity and egg fertilization rate. A total of 24 male and 72 female geese, all 180-days-old, were selected and divided into four treatment groups, each with a consistent body weight. Each treatment group had six male and 18 female geese (1:3 ratio of male to female). The control (Ⅰ) group was fed a basal diet. The YS (Ⅱ) group was fed a basal diet supplemented with 0.3 mg/kg of selenium-yeast. The ZL (Ⅲ) group was fed a basal diet supplemented with 106.05 mg/kg of zinc-lysine. The YS + ZL (Ⅳ) group was fed a basal diet supplemented with 0.3 mg/kg of selenium-yeast and 106.05 mg/kg of zinc-lysine. The experimental period lasted for 91 days. The results showed that supplementation of 0.3 mg/kg YS and 106.05 mg/kg ZL significantly increased sperm motility (P < 0.05), and significantly increased VAP, VSL, VCL, ALH, LIN, MAD and STR (P < 0.01) compared with the control group. Compared with the control group, dietary supplementation of YS and ZL increased the number of germ cells and Johnson score in groups Ⅱ, Ⅲ and Ⅳ (P < 0.01), and the number of spermatogonia and sertoli cells were significantly different from the control group (P < 0.05). Dietary supplementation of YS and ZL could increase the reproductive hormone level (P < 0.05) and serum antioxidant capacity (P < 0.05), and the fertilization rate showed a certain promoting trend (P = 0.09). In conclusion, dietary supplementation of 0.3 mg/kg YS and 106.05 mg/kg ZL can improve semen quality, promote testicular development, maintain stability of the fertilization rate, and increase reproductive hormone levels and the serum antioxidant capacity of geese.